Evaluating the Current and Potential Future Increased role of Market-Based Instruments in Promoting the Improved Recycling, Reuse and Reduction of Plastics in South Africa's Circular Waste Economy - Barratt, Kirsten (Department of Public Law, 2023)
It is impossible to imagine life without plastic. Its properties, such as its durability, flexibility and cost-effectiveness have allowed it to dominate almost every industry worldwide. However, its successful properties are also its downfall and have caused them to become a major environmental and human health issue. Plastic waste production across the globe has reached approximately 6300 million metric tonnes, most of which has been disposed of to landfills or more widely into the surrounding environment. South Africa is currently ranked as the 11th worst contributor to mismanaged plastic waste in the oceans and, while its domestic legislation is good, it does not seem to be doing enough to keep plastic out of the environment. South Africa's virgin plastic consumption grew to around 1.544 million metric tonnes in 2018 and approximately 53% of that total consumption goes into the packaging sector. Most of this is used for single-use packaging applications, which is the largest component of plastic waste generated in South Africa. This valuable material needs to be kept in the circular economy where it can be reused and recycled. There are two main types of legal mechanisms to help curb environmental pollution and promote more sustainable approaches to management: command and control measures and market-based instruments (MBIs). South Africa has relied heavily on command-andcontrol measures. Command-and-control measures involve the direct regulation of activities or unwanted items through legislation, and MBIs aim to influence human behaviour through the use of economic incentives or disincentives. This dissertation focuses on the options that exist for South Africa to improve and expand the use of MBIs to promote better recycling, reuse, and reduction of plastics in its circular waste economy. It focuses on MBIs because South Africa is a developing country with limited resources and MBIs have been identified by commentators as more cost-effective than the traditional command-and-control approach. It focuses on an expansion of existing MBIs (as the current MBIs do not seem to be doing enough to keep plastic out of the environment), as well as looks towards new possible MBIs to implement in the future through the legal regime. It ultimately concludes that MBIs are a viable option for South Africa and that the Republic could do more to implement them into the regulatory regime to move from a linear economy to a circular economy.